A study into the effects of deregulation of the New Zealand petrol industry : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Applied Economics - Wheeler, Cameron John (Massey University, 1999)
The overall objective of this thesis is to investigate the effects of deregulation of the New Zealand petrol industry. Various economic theories are presented in an effort to help the reader better understand the industry, and to explain its workings. The legislative background is discussed, and areas looked at cover the structure, conduct, and performance of the industry and its participants, both prior to, and after deregulation. An econometric analysis of the industry is also conducted.
Keywords: Petroleum industry and trade -- Deregulation; New Zealand